High intensity interval exercise decreases IL-8 and enhances the immunomodulatory cytokine interleukin-10 in lean and overweight–obese individuals - Dorneles, Gilson P.; Haddad, Desirée O.; Fagundes, Viviane O.; Vargas, Bruna K.; Kloecker, Alana; Romão, Pedro R.T.; Peres, Alessandra (Cytokine (Philadelphia, Pa.), 2016)
•Obese individuals exhibit a low grade systemic inflammatory profile.•High intensity interval exercise (HIIE) decreased IL-8 levels in lean and obese.•HIIE increased systemic levels of IL-6 and IL-10 in lean and obese.•HIIE may help reduce low grade inflammation in obesity.•Moderate exercise had no effects in acute cytokine response in both groups. To compare the effects of two interval exercises with different intensities on acute inflammatory response in lean and overweight–obese subjects. Ten lean (BMI<24.9kg/m2) and 12 overweight–obese (BMI 25 to <34.9kg/m2) males performed two conditions in randomly assigned: (1) high intensity interval exercise (HIIE) 10×60s (85–90%PMax)/75s (50%PMax); (2) moderate intensity interval exercise (MIIE) 10×60s (70–75%PMax)/60s (50%PMax), with blood collections at pre, immediately and 30min post each exercise bouts to evaluate total and differential leukocyte counts, serum creatine kinase (CK), lactate dehydrogenase (LDH) and systemic levels of IL-1ra, IL-6, IL-8, IL-10, IL-17a and CCL2. In lean group, HIIE induced a significant increase in total leukocytes and monocyte, while MIIE session did not change the number of leukocytes. Overweight–obese group presented similar increase in leukocytes, monocytes and lymphocytes in both HIIE and MIIE sessions. At baseline, overweight–obese group showed high levels of CK, IL-8, IL-6 and CCL2 and lower concentrations of IL-10 compared to lean group. The MIIE did not alter the cytokine concentrations in both groups, independently of the time analysis. The HIIE induced significant decrease in IL-8 levels 30min post session in both the groups, and a progressive elevation in IL-10 levels immediately and 30min post in lean and overweight–obese. Regarding IL-6, overweight–obese subjects presented progressive increase either immediately and 30min after HIIE, while lean individuals presented significant increase only 30min after exercise. The acute inflammatory response to interval exercise is intensity-dependent. Although obesity influences the basal concentrations of several cytokines, only HIIE induced important alterations in IL-8 and IL-10 levels, which may have important implications in the control of chronic low-grade inflammation in obesity.